Pitstop approach: diabetologist referral and quality of care in patients with type 2 diabetes – a Swiss longitudinal study (Swiss Medical Weekly, 2025)
STUDY AIMS: Patients with type 2 diabetes mellitus are typically managed in primary care settings, but management has become more complex in recent years due to modern therapeutic options. There is a paucity of data on the role of a one-off referral to an outpatient diabetes centre (a “pitstop” approach) in improving the quality of diabetes care.METHODS: This was a retrospective study of patients with type 2 diabetes mellitus who were referred to an outpatient diabetes centre at a regional hospital in Switzerland between 1 January 2019 and 31 December 2020. The primary outcome was the change in glycated haemoglobin (HbA1c) between the first and last consultation. Secondary endpoints included changes in body weight, blood pressure, low-density lipoprotein cholesterol and use of antidiabetic medications.RESULTS: At a median follow-up of 5.1 months (interquartile range [IQR] 3.0–9.1) after referral to an outpatient diabetes centre, haemoglobin A1c improved from 8.6% / 70.5 mmol/mol to 7.3% / 56.3 mmol/l (difference −1.28% / −14.2 mmol/l; 95% confidence interval [CI] −1.50 to −1.05), body weight decreased from 91.0 kg to 88.0 kg (difference −3.93; 95% CI −4.9 to −3.0) and systolic blood pressure values decreased by 1.6 mm Hg (95% CI −2.7 to −0.5), while low-density lipoprotein cholesterol levels remained unchanged. Compared to baseline, the pitstop approach resulted in decreased prescriptions for sulfonylureas (11.0% vs 2.8%) and dipeptidyl peptidase-4 inhibitors (31.4% vs 20.0%), but increased prescriptions for sodium-glucose cotransporter 2 (SGLT2) inhibitors (15.3% vs 27.5%) and glucagon-like peptide-1 (GLP1) receptor agonists (13.7% vs 46.3%).CONCLUSION: A short-term intervention by an outpatient diabetes clinic was associated with significant improvements in glycaemic control and body weight in patient with type 2 diabetes. It promoted a shift towards modern antidiabetic medications with proven cardiorenal protective effects.